Buddhist legends - Buddhaghosa.; Burlingame, Eugene Watson; Lanman, Charles Rockwell (Harvard university press, 1921)
pt. 1. Introduction; synopses; translation of books 1 and 2.--pt. 2. Translation of books 3 to 12.--pt. 3. Translation of books 13 to 26.